Breakeven, Cost Benefit, Cost Effectiveness, and Willingness to Pay for Web-Based Versus Face-to-Face Education Delivery for Health Professionals - Maloney, Stephen; Haas, Romi; Keating, Jenny L; Molloy, Elizabeth; Jolly, Brian; Sims, Jane; Morgan, Prue; Haines, Terry (JMIR Publications, 2012)
BackgroundThe introduction of Web-based education and open universities has seen an increase in access to professional development within the health professional education marketplace. Economic efficiencies of Web-based education and traditional face-to-face educational approaches have not been compared under randomized controlled trial conditions. ObjectiveTo compare costs and effects of Web-based and face-to-face short courses in falls prevention education for health professionals. MethodsWe designed two short courses to improve the clinical performance of health professionals in exercise prescription for falls prevention. One was developed for delivery in face-to-face mode and the other for online learning. Data were collected on learning outcomes including participation, satisfaction, knowledge acquisition, and change in practice, and combined with costs, savings, and benefits, to enable a break-even analysis from the perspective of the provider, cost-effectiveness analysis from the perspective of the health service, and cost-benefit analysis from the perspective of the participant. ResultsFace-to-face and Web-based delivery modalities produced comparable outcomes for participation, satisfaction, knowledge acquisition, and change in practice. Break-even analysis identified the Web-based educational approach to be robustly superior to face-to-face education, requiring a lower number of enrollments for the program to reach its break-even point. Cost-effectiveness analyses from the perspective of the health service and cost-benefit analysis from the perspective of the participant favored face-to-face education, although the outcomes were contingent on the sensitivity analysis applied (eg, the fee structure used). ConclusionsThe Web-based educational approach was clearly more efficient from the perspective of the education provider. In the presence of relatively equivocal results for comparisons from other stakeholder perspectives, it is likely that providers would prefer to deliver education via a Web-based medium. Trial RegistrationAustralian New Zealand Clinical Trials Registry (ACTRN): 12610000135011; http://www.anzctr.org.au/trial_view.aspx?id=335135 (Archived by WebCite at http://www.webcitation.org/668POww4L)